2016
DOI: 10.17159/1947-9417/2015/555
|View full text |Cite
|
Sign up to set email alerts
|

The possible influence of curriculum statements and textbooks on misconceptions: The case of evolution

Abstract: Curriculum statements and textbooks are considered to be vital support tools for teachers, particularly during times of curriculum innovation. A recent change in South Africa was the controversial inclusion of evolution in the school curriculum, raising serious concerns amongst biology teachers regarding the adequacy of their content and pedagogical content knowledge for teaching the topic. Widespread 'misconceptions' about evolution make teaching this topic difficult for biology teachers worldwide. Identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 25 publications
0
35
0
3
Order By: Relevance
“…The remaining 13 publications are journal articles. Of these, three studies analysed the influence of textbooks and the curriculum statement on learning evolution 5,14,17 ; four focused on teacher reactions to and acceptance of teaching evolution 1,3,4,11 ; and six studies reported on student reactions to, and acceptance of learning about, evolution 8,15,16,[18][19][20] .…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining 13 publications are journal articles. Of these, three studies analysed the influence of textbooks and the curriculum statement on learning evolution 5,14,17 ; four focused on teacher reactions to and acceptance of teaching evolution 1,3,4,11 ; and six studies reported on student reactions to, and acceptance of learning about, evolution 8,15,16,[18][19][20] .…”
Section: Reviewmentioning
confidence: 99%
“…In analyses of textbooks and curriculum statements 5,14,17 , it has been found that the evolution curriculum and the evolution content in textbooks often achieve the opposite of what is desired: that is, they perpetuate misconceptions and unscientific ideas about evolution by using improper and misleading terminology and by reporting inaccurate information.…”
Section: Research Based On Text Analysesmentioning
confidence: 99%
See 3 more Smart Citations